Survey and Comparative Study on Agile Methods in Software Engineering - El Mehdi, Achrak; Yassin, Chkouri Mohamed; Kamal Eddine, El Kadiri (Transactions on Engineering and Computing Sciences, 2017)
Today‘s business environment is very much dynamic, and organisations are constantly changing their software requirements to adjust with new environment. They also demand for fast delivery of software products as well as for accepting changing requirements. In this aspect, traditional plan-driven developments fail to meet up these requirements. Though traditional software development methodologies, such as life cycle-based structured and object oriented approaches, continue to dominate the systems development few decades and much research has done in traditional methodologies, Agile software development brings its own set of novel challenges that must be addressed to satisfy the customer through early and continuous delivery of the valuable software. This article is located in the field of engineering Information Systems (IS) and in particular in the world of engineering process. In order, to produce information systems that the customer needs, many methods engineering were introduced. The first methods introduced are called sequential methods like Cascade method, V cycle or the Y cycle then there are iterative methods like RUP or Symphony and finally agile methods like Scrum and XP have emerged.